Gender influence on antioxidant capacity and oxidative damage in saliva of children with autism spectrum disorder: a preliminary study - Matheus Morcela De SOUZA; João Victor Soares RODRIGUES; Maria Eduarda CABRERIZO GONÇALVES; Ana Carolina Polanowski ROSSATO; Maria Cristina Ruiz VOMS STEIN; Maria Clara Faria POLI; Letícia Helena THEODORO; Ana Cláudia de Melo Stevanato NAKAMUNE (Universidade Estadual Paulista, 2021)
Abstract Introduction Autism is a complex neurological disorder with multifactorial causes, which compromises physical, psychological, emotional and social skills. This disorder also impairs dental care and patient oral health. Saliva can be easily obtained using a non-invasive technique and has been used in the diagnosis and screening of many pathologies. Total antioxidant capacity of saliva is reduced in the presence of caries in children and has been studied as a possible marker for autism. However, data on salivary antioxidants in children with autism spectrum disorder (ASD) is scarce. Objective This preliminary study evaluated the existence of gender influence on non-enzymatic antioxidant capacity and protein oxidative damage in the saliva of children with this disorder. Our hypothesis is that there are gender differences in these biochemical parameters in children with austim. Material and method Whole saliva samples were collected by aspiration between 8:00-11:00 am from 12 girls and 12 boys aged 5 to 15 years, with previous diagnosis for this disorder. Total antioxidant capacity, uric acid, protein concentration and oxidative damage to proteins were analyzed by spectrophotometry. Values were presented as mean ± standard deviation and tested for adherence to normality (Shapiro-Wilk test). The data were then compared using the Mann-Whitney test, considering a 5% significance level. Result There was no significant difference between groups for all analyzed parameters (P>0.05). Conclusion Based on the results obtained, we concluded that gender does not influence the levels of oxidative stress markers in the saliva of children with ASD.